2011
DOI: 10.1111/j.1365-2788.2011.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality outcomes in group home dementia care for adults with intellectual disabilities

Abstract: It is proposed that efforts to evaluate dementia-related care provision with respect to quality need to consider quality of care provision components such as (1) clinically relevant early and periodic assessment; (2) functional modifications in the living setting; (3) constructive staff education and functionality for stage-adapted care; and (4) flexible long-term services provision that recognises and plans for progression of decline and loss of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 40 publications
1
52
0
1
Order By: Relevance
“…quality of care SCHAAP et Al. dementia (Cleary & Doodey, 2016;Duggan et al, 1996;Emerson, 2001;Iacono, Bigby, Carling-Jenkins, & Torr, 2014;Myrbakk & von Tetzchner, 2008); they tend to use an ad hoc approach (Iacono et al, 2014;Janicki, 2011;Janicki, McCallion, & Dalton, 2002;Watchman, 2008;Wilkinson, Kerr, & Cunningham, 2005). Therefore, an evidence-based method that provides insights, knowledge and skills for professionals in the care of older residents with intellectual disability and dementia is urgently needed, but not yet available.…”
mentioning
confidence: 99%
“…quality of care SCHAAP et Al. dementia (Cleary & Doodey, 2016;Duggan et al, 1996;Emerson, 2001;Iacono, Bigby, Carling-Jenkins, & Torr, 2014;Myrbakk & von Tetzchner, 2008); they tend to use an ad hoc approach (Iacono et al, 2014;Janicki, 2011;Janicki, McCallion, & Dalton, 2002;Watchman, 2008;Wilkinson, Kerr, & Cunningham, 2005). Therefore, an evidence-based method that provides insights, knowledge and skills for professionals in the care of older residents with intellectual disability and dementia is urgently needed, but not yet available.…”
mentioning
confidence: 99%
“…Janicki () found several factors that impacted where adults with intellectual disabilities and dementia were cared for or transitioned to in a review of the literature and policy and practice organizational guidelines. While adults with intellectual disabilities and dementia often remained in their community residences with supports, for some there was a “tipping point” at which they would be moved (p. 757).…”
Section: Resultsmentioning
confidence: 99%
“…A lack of staff training might directly impact the end of life for people with intellectual disabilities if they are being transitioned from their agency residences when the staff feel unable to provide care (Bekkema, de Veer, Wagemans, Hertogh, & Francke, ; Bigby et al., ; Janicki, ; McCarron, McCallion, Fahey‐McCarthy, & Connaire, ; Webber, Bowers, & McKenzie‐Green, ). The present authors identified two published reports of training programmes designed for staff providing disability services to adults with intellectual disabilities and life‐limiting conditions (Fahey‐McCarthy et al., ; Hahn & Cadogan, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the average age of onset is significantly influenced by the presence or absence of DS. Lai (1992) reported an average age of onset for those with DS between 51 and 54 years of age, whereas individuals with ID without DS are diagnosed after the age of 65 on average (Janicki andDalton 1993, 2000;Lai and Williams 1989). Behavior change is often observed prior to the observation of cognitive decline .…”
Section: Dementia In Down Syndromementioning
confidence: 99%